Desertification gradients shape Medicago sativa rhizosphere microbiomes in inner Mongolia’s agro-pastoral ecotone - Xu, Jiajia; Wang, Senyuan; Jia, Zhenyu; Wang, Zhaoming; Bao, Yuying; Wei, Jie (Frontiers in Microbiology, 2025)
This study investigated the spatial heterogeneity of rhizosphere microbial communities in alfalfa (Medicago sativa) across desertification gradients in Inner Mongolia, China. Rhizosphere soils were collected from non-, lightly-, and moderately- desertified sites. Using 16S rRNA and ITS high-throughput sequencing alongside soil physicochemical analyses, we found that desertification intensity significantly altered microbial structure and function. Actinobacteriota dominated in moderately-desertified soils, whereas Proteobacteria prevailed in non-desertified areas. Ascomycota was the dominant fungal phylum, with Basidiomycota and Mortierellomycota enriched in non- and lightly- desertified sites, respectively. Soil pH and available phosphorus were the key factors shaping bacterial and fungal communities, respectively. Co-occurrence networks indicated enhanced microbial connectivity and a shift toward cooperative interactions under desertification. Functional prediction revealed conserved bacterial metabolic pathways but increased abundance of fungal stress-response enzymes (e.g., monooxygenases). These findings underscore microbial adaptive strategies to desertification and provide insights for sustainable agriculture in arid regions.